The effect of different starting procedures on sprinters` reaction time - Haugen, T. A.; Shalfawi, S.; Tonnessen, E. (Journal of Sports Sciences, 2013)
We examined the effect of different false start rules and starters` holding time on athletics sprinters` reaction times. Reaction times from 210 female (25.2 ± 3.8 years) and 361 male (24.8 ± 3.8 years) 100 m sprinters, participating in international championships for seniors from 1997 to 2011, were analysed. Holding time calculations were based on television recordings from the analysed heats (n = 267). Mean reaction times have increased by 20% (0.03 s, P < 0.001) during a 15 year period due to stricter false start rules. Starters` holding times were between 1.3 and 2.2 s for the analysed competitions. There was a small but significant relationship between reaction time and starters` holding time for men (r = 0.16, P < 0.001) and women (r = 0.17, P < 0.001) between 1997 and 2003 and for men (r = 0.16, P < 0.001) in the time period 2003-2009, but not for women in the time period 2003-2009. While the interquartile range of reaction time decreased with longer holding time for female sprinters, the opposite trend was observed among the males. The present study demonstrates that world class sprinters` reaction times and thereby their 100 m performance can vary 0.03-0.05 s depending on false start regulations and holding time.